Impact on Soybean Yield from Sudden Death Syndrome and Soybean Planting Date - E. A. Adee; C. Little; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2018)
Sudden Death Syndrome (SDS) is a disease caused by the soilborne fungusFusarium virguliforme. This fungus prefers wet conditions and thus is usually most severe in irrigated fields. SDS tends to be most severe on well-managed soybeans with a high yield potential. It also tends to be more prevalent on fields that are infested with soybean cyst nematode (SCN) or planted early when soils are wet and cool. Historical yield losses from this disease are generally in the range of 1–25%. Soybean planting dates have been moving increasingly earlier in much of the soybean growing region, including Kansas. Yield loss of up to 0.5 bushel per day is not uncommon when soybeans are planted after May 10 in many soybean growing regions. However, in the Kansas River Valley, many of the soybeans have been planted after mid-May because of the perennial problem with SDS on soybeans. Later planting has been prescribed as a management practice to help avoid the cooler/wetter soils that can create greater probability of infection by the fungus.
Keywords: Sudden Death Syndrome; soybean; planting date; Fusarium virguliforme